Structural, spectroscopic, and kinetic investigation of the molybdenum dialkylhydrazido complexes [MoBr(NNC5H10)(dppe) 2]Br and [Mo(NNC5H10)(dppe)2]: Activation parameters and revised mechanism for N-N cleavage - Dreher, Ameli; Mersmann, Klaus; Näther, Christian; Ivanovic-Burmazovic, Ivana; van Eldik, Rudi; Tuczek, Felix (Inorganic Chemistry, 2009)
The reaction of [Mo(NNCH)(dppe)] (B) with an excess of acid, HNEtBPh, is investigated applying temperature-dependent stopped-flow measurements. The kinetic data indicate a biphasic process with rate constants k and K which are both slower than the single rate constant reported by Henderson et al. (Henderson, R. A.; Leigh, G. J.; Pickett, C. J., J, Chem. Soc., Dalton Trans. 1989, 425-430). Moreover, both rate constants exhibit a linear dependence on the acid concentration with a large intercept which is attributed to acid-dependent and acid-independent components of each reaction phase, respectively. All four reaction channels exhibit temperature-dependent reaction rates. Furthermore, B and its Mo(IV) analogue [MoBr(NNCH)(dppe)]Br (A) are characterized structurally and spectroscopically. Density-functional theory calculations are performed to locate possible barriers in the overall reaction scheme and determine their energies, providing additional information for the formulation of a mechanism. The temperature-dependent rate of N-N cleavage is explained by a revised mechanism which involves an α-protonated intermediate that is inert with respect to N-N cleavage and is generated from its β-protonated counterpart by a rapid 1,2-proton shift. The implications of these results with respect to N reduction in the Chatt cycle and the enzyme nitrogenase are discussed. © 2009 American Chemical Society.